Contemporary ideas on ship stability and capsizing in waves - Almeida Santos Neves, Marcelo; SpringerLink (Online service). (Dordrecht New York Springer Science+Business Media B.V., 2011)
During the last decade significant progress has been made in the field of ship stability.Yet in spite of the progress made, numerous scientific and practical challenges still exist with regard to the accurate prediction of extreme motion and capsize dynamics for intact and damaged vessels, the probabilistic nature of extreme events, criteria that properly reflect the physics and operational safety of an intact or damaged vessel, and ways to provide relevant information on safe ship handling to ship operators. This book provides a comprehensive review of the above issues through the selection of representative papers presented at the unique series of international workshops and conferences on ship stability held between 2000 and 2009. The editorial committee has selected papers for this book from the following events: STAB 2000 Conference (Launceston, Tasmania), 5th Stability Workshop (Trieste, 2001), 6th Stability Workshop (Long Island, 2002), STAB 2003 Conference (Madrid), 7th Stability Workshop (Shanghai, 2004), 8th Stability Workshop (Istanbul, 2005), STAB 2006 Conference (Rio de Janeiro), 9th Stability Workshop (Hamburg, 2007), 10th Stability Workshop (Daejeon, 2008), and STAB 2009 Conference (St. Petersburg).   The papers have been clustered around the following themes: Stability Criteria, Stability of the Intact Ship, Parametric Rolling, Broaching, Nonlinear Dynamics, Roll Damping, Probabilistic Assessment of Ship Capsize, Environmental Modelling, Damaged Ship Stability, CFD Applications, Design for Safety, Naval Vessels, and Accident Investigations.
Preface -- 1 Stability Criteria -- Review of Available Methods for Application to Second Level Vulnerability Criteria, by Christopher C. Bassler, Vadim Belenky, Gabriele Bulian, Alberto Francescutto, Kostas Spyrou and Naoya Umeda -- A Basis for Developing a Rational Alternative to the Weather Criterion: Problems and Capabilities , by K. J. Spyrou -- Conceptualising Risk, by Andrzej Jasionowski and Dracos Vassalos -- Evaluation of the Weather Criterion by Experiments and its Effect to the Design of a Ro-Pax Ferry, by Shigesuke Ishida, Harukuni Taguchi and Hiroshi Sawada -- Evolution of Analysis and Standardization of Ship Stability: Problems and Perspectives, by Yury Nechaev -- SOLAS 2009 ? Raising the Alarm, by Dracos Vassalos and A. Jasionowski -- 2 Stability of the Intact Ship --  Effect of Initial Bias on the Roll Response and Stability of Ships in Beam Seas, by A. Y. Odabasi and E. Ucer -- Historical Roots of the Theory of Hydrostatic Stability of Ships, by Horst Nowacki and Larrie D. Ferreiro -- The Effect of Coupled Heave/Heave Velocity or Sway/Sway Velocity Initial Conditions on Capsizing Modelling, by Leigh S. McCue and Armin W. Troesch -- The Use of Energy Build Up to Identify the Most Critical Heeling Axis Direction for Stability Calculations for Floating Offshore Structures, by Joost van Santen -- Some Remarks on Theoretical Modelling of Intact Stability, by N. Umeda, Y. Ohkura, S. Urano, M. Hori and H. Hashimoto -- 3 Parametric Rolling -- An Investigation of Head-Sea Parametric Rolling for Two Fishing Vessels, by Marcelo A. S. Neves, Nelson A Pérez, Osvaldo M Lorca and Claudio A Rodriguez -- Simple Analytical Criteria for Parametric Rolling, by K.J. Spyrou -- Experimental Study on Parametric Roll of a Post-Panamax Containership in Short-Crested Irregular Waves, by Hirotada Hashimoto, Naoya Umeda and Akihiko Matsuda -- Model Experiment on Parametric Rolling of a Post-Panamax Containership in Head Waves, by Harukuni Taguchi, Shigesuke Ishida, Hiroshi Sawada and Makiko Minami -- Numerical Procedures and Practical Experience of Assessment of Parametric Roll of Container Carriers, by Vadim Belenky, Han-Chang Yu and Kenneth Weems -- Parametric Roll and Ship Design, by Marc Levadou and Riaan van Veer -- Parametric Roll Resonance of a Large Passenger Ship in Dead Ship Condition in All Heading Angles, by Abdul Munif, Yoshiho Ikeda, Tomo Fujiwara and Toru Katayama -- Parametric Rolling of Ships Then and Now, by J. Randolph Paulling -- 4 Broaching-to -- Parallels of Yaw and Roll Dynamics of Ships in Astern Seas and the Effect of Nonlinear Surging, by K.J. Spyrou -- Model Experiment on Heel-Induced Hydrodynamic Forces in Waves for Realising Quantitative Prediction of Broaching, by H. Hashimoto, N. Umeda and A. Matsuda -- Perceptions of Broaching-to: Discovering the Past, by K.J. Spyrou -- 5 Nonlinear Dynamics and Ship Capsizing -- Use of Lyapunov Exponents to Predict Chaotic Vessel Motions, by Leigh S. McCue and Armin W. Troesch -- Applications of Finite-Time Lyapunov Exponents to the Study of Capsize in Beam Seas, by Leigh S. McCue -- Nonlinear Dynamics on Parametric Rolling of Ships in Head Seas, by Marcelo A. S. Neves, Jerver E. M. Vivanco and Claudio A. Rodríguez -- 6 Roll Damping -- A Simple Prediction Formula of Roll Damping of Conventional Cargo Ships on the Basis of Ikeda's Method and Its Limitation, by Yuki Kawahara, Kazuya Maekawa and Yoshiho Ikeda -- A Study on the Characteristics of Roll Damping of Multi-hull Vessels, by Toru Katayama, Masanori Kotaki and Yoshiho Ikeda -- 7 Probabilistic Assessment of Ship Capsize -- Capsize Probability Analysis for a Small Container Vessel, by E.F.G. van Daalen, H. Boonstra and J.J. Blok -- Efficient Probabilistic Assessment of Intact Stability, by N. Themelis and K.J. Spyrou -- Probability of Capsizing in Beam Seas with Piecewise Linear Stochastic GZ Curve, by Vadim Belenky, Arthur M. Reed and Kenneth M. Weems -- Probabilistic Analysis of Roll Parametric Resonance in Head Seas, by Vadim L. Belenky, Kenneth M. Weems, Woei-Min Lin and J.Randolf Paulling -- 8 Environmental Modeling -- Sea Spectra Revisited, by Maciej Paw?owski -- On Self-Repeating Effect in Reconstruction of Irregular Waves, by Vadim Belenky -- New Approach To Wave Weather Scenarios Modeling, by Alexander B.Degtyarev -- 9 Damaged Ship Stability -- Effect of Decks on Survivability of Ro'Ro Vessels, by Maciej Pawowski -- Experimental and Numerical Studies on Roll Motion of a Damaged Large Passenger Ship in Intermediate Stages of Flooding, by Yoshiho Ikeda, Shigesuke Ishida, Toru Katayama and Yuji Takeuchi -- Exploring the Influence of Different Arrangements of Semi-Watertight Spaces on Survivability of a Damaged Large Passenger Ship, by Riaan van 't Veer, William Peters, Anna-Lea Rimpela and Jan Otto de Kat -- Time-Based Survival Criteria for Passenger Ro-Ro Vessels, by Andrzej Jasionowski, Dracos Vassalos and L. Guarin -- Pressure-Correction Method and Its Applications for Time-Domain Flooding Simulation, by Pekka Ruponen -- 10 CFD Applications to Ship Stability -- Applications of 3D Parallel SPH for Sloshing and Flooding, by Liang Shen and Dracos Vassalos -- Simulation of Wave Effect on Ship Hydrodynamics by RANSE, by Qiuxin Gao and Dracos Vassalos -- A Combined Experimental and SPH Approach to Sloshing and Ship Roll Motions, by Luis Pérez-Rojas, Gabriele Bulian, Elkin Botía-Vera, José Luis Cercos-Pita, Antonio Souto-Iglesias and Louis Delorme -- 11 Design for Safety -- Design for Safety with Minimum Life-Cycle Cost, by Romanas Puisa, Dracos Vassalos, Luis Guarin and G. Mermiris  -- 12 Stability of Naval Vessels -- Stability Criteria Evaluation and Performance Based Criteria Development for Damaged Naval Vessels, by Andrew J. Peters and David Wing -- A Naval Perspective on Ship Stability, by Arthur M. Reed -- Accident Investigations -- New Insights on the Sinking of MV Estonia, by Andrzej Jasionowski and Dracos Vassalos -- Experimental Investigation on Capsizing and Sinking of a Cruising Yacht in Wind, by Naoya Umeda, Masatoshi Hori, Kazunori Aoki, Toru Katayama and Yoshiho Ikeda -- Author Index.
Electronic reproduction.
Keywords: Ships -- Hydrodynamics; Stability of ships; Electronic books